Enhanced performance of g-C3N4/TiO2 photocatalysts for degradation of organic pollutants under visible light - Song, G.; Chu, Z.; Jin, W.; Sun, Hongqi (Chemical Industry Press, 2015)
Photocatalytic degradation is one of the most promising remediation technologies in terms of advanced oxidation processes (AOPs) for water treatment. In this study, novel graphitic carbon nitride/titanium dioxide (g-C3N4/TiO2) composites were synthesized by a facile sonication method. The physicochemical properties of the photocatalyst with different mass ratios of g-C3N4 to TiO2 were investigated by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), N2 sorption, Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and UV–vis DRS. The photocatalytic performances were evaluated by degradation of methylene blue. It was found that g-C3N4/TiO2 with a mass ratio of 1.5:1 exhibited the best degradation performance. Under UV, the degradation rate of g-C3N4/TiO2 was 6.92 and 2.65 times higher than g-C3N4 and TiO2, respectively. While under visible light, the enhancement factors became 9.27 (to g-C3N4) and 7.03 (to TiO2). The improved photocatalytic activity was ascribed to the interfacial charge transfer between g-C3N4 and TiO2. This work suggests that hybridization can produce promising solar materials for environmental remediation.